2008
DOI: 10.1359/jbmr.080221
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Genetic Loci for Femoral Neck Bone Mass and Strength Identified in Inbred COP and DA Rats

Abstract: ABSTRACT:Introduction: Hip fracture is the most devastating osteoporotic fracture type with significant morbidity and mortality. Several studies in humans identified chromosomal regions linked to hip size and bone mass. Animal models, particularly the inbred rat, serve as complementary approaches for studying the genetic influence on hip fragility. The purpose of this study is to identify sex-independent and sex-specific quantitative trait loci (QTLs) for femoral neck density, structure, and strength in inbred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Using progeny derived from inbred Fisher 344 and Lewis rats, Alam et al detected significant quantitative trait loci (QTLs) for variation in midshaft femur ultimate force, energy to break, and stiffness [8]; fifth lumbar vertebra ultimate force [8]; and femoral neck ultimate force and energy to break [9]. Studies in another rat model (progeny of Copenhagen 233 and Dark Agouti rats) also revealed QTLs for femoral neck biomechanical properties[10] and femoral midshaft and fifth lumbar vertebra ultimate force [11]. In a study of femurs of HcB/8 and HcB/23 recombinant congenic mice, Saless [12] identified QTLs for total displacement, post yield deflection, and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Using progeny derived from inbred Fisher 344 and Lewis rats, Alam et al detected significant quantitative trait loci (QTLs) for variation in midshaft femur ultimate force, energy to break, and stiffness [8]; fifth lumbar vertebra ultimate force [8]; and femoral neck ultimate force and energy to break [9]. Studies in another rat model (progeny of Copenhagen 233 and Dark Agouti rats) also revealed QTLs for femoral neck biomechanical properties[10] and femoral midshaft and fifth lumbar vertebra ultimate force [11]. In a study of femurs of HcB/8 and HcB/23 recombinant congenic mice, Saless [12] identified QTLs for total displacement, post yield deflection, and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of this literature is devoted to bone mineral density as the phenotype of interest, although an increasing fraction now also addresses bone size as well. Biomechanical performance has been studied as a phenotypic endpoint in only a small number of rodent genetic mapping experiments [717]. The relative dearth of biomechanical genetic investigations reflects the very real barriers to their successful completion: greater technical difficulty, lesser robustness of the phenotypes, and ultimately lesser statistical power to find quantitative trait loci (QTLs).…”
Section: Introductionmentioning
confidence: 99%
“…The use of animal models as a complement to studies in human populations permit identification of candidate genes for additional phenotypes related to bone structure and strength. Inbred rodent strains have been established as valuable models for dissecting the genetic regulation of bone, and several chromosomal regions linked to bone geometry, biomechanics and bone density in distinct trabecular or cortical bone compartments have been identified [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%